2011
DOI: 10.1152/jn.00459.2010
|View full text |Cite
|
Sign up to set email alerts
|

GABAB receptor-mediated tonic inhibition of noradrenergic A7 neurons in the rat

Abstract: Noradrenergic (NAergic) A7 neurons that project axonal terminals to the dorsal horn of the spinal cord to modulate nociceptive signaling are suggested to receive tonic inhibition from local GABAergic interneurons, which are under the regulation of descending analgesic pathways. In support of this argument, we presently report GABA(B) receptor (GABA(B)R)-mediated tonic inhibition of NAergic A7 neurons. Bath application of baclofen induced an outward current (I(Bac)) in NAergic A7 neurons that was blocked by CGP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 61 publications
2
18
0
Order By: Relevance
“…For example, since ambient GABA levels in the LC are significantly higher during REM/non-REM sleep than during wakefulness (Nitz & Siegel, 1997;Nelson et al 2002), our results suggest that GABA B R-mediated tonic inhibition may play an important role in regulating the SFR of LC neurons, and thus the wakefulness/arousal level of the brain. In addition to postsynaptic regulation, GABA B Rs at presynaptic sites have been shown to regulate glutamate and GABA release in many brain areas (Wu et al 2011;Wang et al 2013), perhaps including the LC neurons, as our EM study showed presynaptic location of GABA B Rs in the LC. As GABA B R signalling and the activity of GABA transporters in many physiological and pathological processes can be regulated by various transmitter/receptor systems, such as the activation of 5-HT 1A receptors during chronic exposure to SSRIs, our results suggest that tonic inhibition and presynaptic regulation of transmitter release mediated by peri/extrasynaptic GABA B Rs on LC neurons could be important players in the development of normal and abnormal behaviours/brain functions that are associated with the LC-NA system.…”
mentioning
confidence: 55%
See 4 more Smart Citations
“…For example, since ambient GABA levels in the LC are significantly higher during REM/non-REM sleep than during wakefulness (Nitz & Siegel, 1997;Nelson et al 2002), our results suggest that GABA B R-mediated tonic inhibition may play an important role in regulating the SFR of LC neurons, and thus the wakefulness/arousal level of the brain. In addition to postsynaptic regulation, GABA B Rs at presynaptic sites have been shown to regulate glutamate and GABA release in many brain areas (Wu et al 2011;Wang et al 2013), perhaps including the LC neurons, as our EM study showed presynaptic location of GABA B Rs in the LC. As GABA B R signalling and the activity of GABA transporters in many physiological and pathological processes can be regulated by various transmitter/receptor systems, such as the activation of 5-HT 1A receptors during chronic exposure to SSRIs, our results suggest that tonic inhibition and presynaptic regulation of transmitter release mediated by peri/extrasynaptic GABA B Rs on LC neurons could be important players in the development of normal and abnormal behaviours/brain functions that are associated with the LC-NA system.…”
mentioning
confidence: 55%
“…We refer to this GABA B R antagonist‐induced current as the GABA B R‐mediated standing current (GABA B R‐ I Stand ) (see Wu et al . ). Since CGP54626 and SCH50911 both function as inverse agonists of GABA B Rs (Grünewald et al .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations